1994
DOI: 10.1039/ft9949001473
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low temperature kinetics of neutral–neutral reactions: rate constants for the reactions of OH radicals with butenes between 295 and 23 K

Abstract: The first experiments on the kinetics of reactions of the OH radical at temperatures below 80 K are reported. They have been carried out by applying t h e pulsed laser photolysis (PLP), laser-induced fluorescence (LIF) technique for studying the kinetics of free radical reactions in t h e ultracold environment provided by the gas flow in a CRESU (Cinetique de Reaction en Ecoulement Supersonique Uniforme) apparatus. This method has yielded rate constants for the reactions of OH with but-1-ene, (Z)-but-2-ene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
87
0
7

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(106 citation statements)
references
References 35 publications
12
87
0
7
Order By: Relevance
“…Reactions of the CN radical were the first to be investigated in the CRESU apparatus in Rennes (Sims et al 1994b). The rate coefficients obtained (Sims et al 1993b) for their reaction with C2H2 are shown in Fig.…”
Section: Review Of Results On Low Temperature Reactionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Reactions of the CN radical were the first to be investigated in the CRESU apparatus in Rennes (Sims et al 1994b). The rate coefficients obtained (Sims et al 1993b) for their reaction with C2H2 are shown in Fig.…”
Section: Review Of Results On Low Temperature Reactionsmentioning
confidence: 99%
“…Over the past 4 years, the PLP-LIF technique has been implemented in the super-cold environment provided in a CRESU apparatus (Sims & Smith 1995, Sims et al 1994b. The CRESU apparatus, originally devised to study ion-molecule reactions under thermally equilibrated conditions at temperatures down to 8 K , Rowe et al 1987), has at its heart a Laval nozzle (see Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations